Kontribusi konsep diri terhadap motivasi belajar siswa di sekolah - Heru Sriyono (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Potential learners that must be built up not merely deals with the issue of intelligence and skills, but involves all forms of personality and self-concept and learning motivation. The purpose of this study is to determine the contribution given by self-concept variable to student's motivation variable. This research is a correlational research involving 40 students in SMA N 64 Jakarta. Data analysis was performed by simple linear regression technique. The findings of this research is that there is a significant relationship between self-concept and student learning motivation. The contribution of self-concept to student's learning motivation is still relatively small in this research, that is 6%.